Toward a conceptual approach for assessing risks from chemical mixtures and other stressors to coastal ecosystem services. (1st November 2016) - Syberg, Kristian; Backhaus, Thomas; Banta, Gary; Bruce, Peter; Gustavsson, Mikael; Munns, Wayne R; Rämö, Robert; Selck, Henriette; Gunnarsson, Jonas S
ABSTRACT: Growth of human populations and increased human activity, particularly in coastal areas, increase pressure on coastal ecosystems and the ecosystem services (ES) they provide. As a means toward being able to assess the impact of multiple stressors on ES, in the present study we propose an 8‐step conceptual approach for assessing effects of chemical mixtures and other stressors on ES in coastal areas: step A, identify the relevant problems and policy aims; step B, identify temporal and spatial boundaries; step C, identify relevant ES; step D, identify relevant stressors (e.g., chemicals); step E, translate impacts into ES units; step F, assess cumulative risk in ES units; step G, rank stressors based on their contribution to adverse effects on ES; and step H, implement regulation and management as appropriate and necessary. Two illustrative case studies (Swedish coastal waters and a coastal lagoon in Costa Rica) are provided; one focuses on chemicals that affect human food supply and the other addresses pesticide runoff and trade‐offs among ES. The 2 cases are used to highlight challenges of such risk assessments, including use of standardized versus ES‐relevant test species, data completeness, and trade‐offs among ES. Lessons learned from the 2 case studies are discussed in relation to environmental risk assessment and management of chemical mixtures. Integr Environ Assess Manag 2017;13:376–386. © 2016 SETAC Key Points: Coastal areas are under increased pressure from human activities. Chemical mixtures are among the most important stressors in coastal areas. Ecosystem services can be used as a unit to assess the impact of multiple stressors. We introduce a 7‐step approach for linking chemical mixtures to ecosystem services in coastal areas.